2015
DOI: 10.2749/222137815818357403
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and Parametric modeling in the Conceptual Design of Bridges

Abstract: <p>Parametric techniques are developing as an agile tool in both civil engineering and architectural design. What is especially powerful is the ability of these softwares to relate and iterate through multiple options with minimal effort. The tools that combine a parametric definition of the bridge with a 3D graphic and a FEM model gives the designer the opportunity to analyse instantaneously, the effect in the variation of the variable parameters in terms of visual appearance as well as structural behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…According to Romo et al (2015), the typical structural engineering workflow shown in Figure 2 first requires the development of a concept for the structural system. Predetermined standards within an organisation (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Romo et al (2015), the typical structural engineering workflow shown in Figure 2 first requires the development of a concept for the structural system. Predetermined standards within an organisation (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…culvert design coefficient tables) (Reynolds et al 2007) are often used to develop the conceptual structural system. Depending on the preferred structural analysis tool, a 3D finite element analysis (FEA) model can be generated to visualise the preliminary design geometry for correctness (Romo et al 2015). Moreover, the preference of FEA tools is based on the ability to produce accurate and realistic analysis results, which may lead to a more economical design.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations